Eroticism, the poetics of emptiness and avant-garde sublimity in Altazor by Vicente Huidobro - Ortiz Aguirre, Enrique (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Altazor o el viaje en paracaídas by Vicente Huidobro is undoubtedly one of the masterpieces of Spanish-American literature and, by extension, of Hispanic-American literature. Inquiring into its literary construction from the avant-garde codes of eroticism as a trigger, and the aesthetics of sublimity as a framework of creation, is the best way to understand the poetics of emptiness and the systematisation of literary resources that articulate the sublime. Thus, creationism singularly and the avant-gardes in general, find their entropic demiurge in the dissolution of limits that energises sublimity.